Albanian literacy at preuniversity Albanian students - Lamçja, Dhurata; Poroçani, Natasha (Edelweiss Applied Science and Technology, 2024)
This paper explores the assessment practices and educational frameworks surrounding Albanian language and literature education, particularly focusing on the National Exams Final Test in Albania. It critically examines how this examination evaluates students' communication skills and linguistic competencies, comparing these practices with those in Kosovo and across Europe. Emphasizing the integration of high-quality texts and cultural identity in educational assessments, the study advocates for enhancements in curriculum design and evaluation criteria. By proposing recommendations for refining the State Exams process, the paper aims to align educational standards with contemporary practices while reinforcing cultural identity within a multicultural context.